PATTERNS OF SHORT-TERM BLOOD PRESSURE VARIABILITY BY AGE IN SERIES OF EXAMS CARRIED DURING TWENTY-FIVE YEARS. (June 2022) - Sousa, Andréa Cristina; Magalhães, Fabrício Galdino; Silva, Suelen Benta; Simeoni, Adélia Rocha; Inuzuka, Sayuri; Batista, Sandro Rogério; Vale, Raquel Mendonça; Amaral, Monica Santos; Souza, Weimar Kunz Barroso; Sousa, Ana Luiza Lima
Abstract : Objective: To describe patterns of short-term blood pressure variability and the association with age. Design and method: Cross-sectional study, with series of exams executed during 25 years. Variables used: gender, age, blood pressure values in different periods, nocturnal drop, coefficient of variation (CV) and standard deviation; normal nocturnal drop between 10% and 20% of blood pressure reduction, media of 24 hours CV-PAS was used for cutoff point. Effect sizes were calculated for differences in means – of Cohen, performed ANCOVA in all ABPM periods using the covariate sex; significance level for all nalyses 5%. Results: Analyzed 2073 exams, 66.3% of the female sex; medium age 58.3 years (±12.6), 29.4% were older than 65 years. The elderly, in all periods, had higher SBP media and lower of DBP. The elderly showed less BP control during nighttime (27.3%) than adults (35.3%) and more absence of nighttime drop (83.5%). Nocturnal drop in elderly was 17.7%/systolic and 36.6%/diastolic; in adults was 26.8%/52.1%, respectively. The Systolic Coefficient of Variation was higher among elderly in the 24hr period 10.8 (±3.1) x 10.0 (±2.4), daytime 10.3 (±2.9) x 9.0 (±2.4) and nighttime 9.0 (±3.0) x 8.6 (±2.8). Conclusions: The elderly had less pressure control during sleep and more absence of nocturnal drop; furthermore, they had a higher Systolic Coefficient of Variation in all periods.